The Effect of Competence, Independence and Work Experience Government Interent Supervisory Apparatus (APIP) on the Effectiveness of Supervision at the Inspectorate of Payakumbuh City - Septian, Andra; Yulihasri (ADPEBI, 2024)
research aims to find and analyze the influence of APIP's competence, independence and work experience on the effectiveness of supervision at the Payakumbuh City Inspectorate. The type of data required in this research is primary data with the data collection method used is using a survey method, namely personal questionnaires (personally administered questionnaires with the respondents being all Payakumbuh City Inspectorate APIPs. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS- SEM) with SmartPLS 4 software to test the proposed structural model and hypothesis. The results show that: 1) APIP competency has a significant influence on the effectiveness of supervision at the Payakumbuh City Inspectorate; 2) APIP independence has a significant influence on the effectiveness of supervision at the Payakumbuh City Inspectorate; and 3) APIP work experience does not have a significant influence on the effectiveness of supervision at the Payakumbuh City Inspectorate.